Designing Vegan Leather Based on Coffee Grounds as an Effort to Optimize Green Brand Awareness Work Unusual - Tamara Cony Widyastika; Arini Arumsari; Muchlis Muchlis (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study addresses the increasing competition in Indonesia's coffee shop industry, where brand identity and sustainability values play a crucial role in building consumer awareness. Work Unusual, a coffee shop that has implemented various sustainability initiatives, faces challenges in communicating these values consistently through its visual media. This research aims to design an apron made of vegan leather from coffee grounds as a product medium to optimize green brand awareness at Work Unusual. A descriptive qualitative approach with a design thinking framework was employed, involving the stages of empathize, define, ideate, prototype, and test. Data were collected through observation, interviews with staff and visitors, questionnaires, and literature studies. The findings reveal that aprons, as staff attributes used in direct customer interactions, hold strategic potential as a visual medium for conveying sustainability values. The use of coffee-grounds-based vegan leather supports material sustainability and circular economy principles while reinforcing brand identity. The apron design successfully integrates function, aesthetics, and eco-friendly values, enhancing consumer perceptions of Work Unusual’s sustainability commitment. This study concludes that sustainable aprons can effectively support the optimization of green brand awareness in coffee shop environments.